Design of regulated ford on the roads of low traffic intensity at the crossing of torrential flows - Đeković Vojislav; Stefanović Bogdan (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu, 2002)
Regulation works in small torrential streams disturb the natural flow regime and the structure of banks and riparian area. The streams are crossed by bridges and culverts. However, at places of low traffic intensity, natural fords are often used for crossing. A regulated ford is constructed by lining and protection of the natural ford, where due to reduced roughness in the ford zone, hydraulic characteristics of the stream show a series of specificities This paper presents the method of calculation of hydraulic factors, which determine the conditions of regulated ford. The construction of regulated ford, as a civil engineering structure, is designed in the conditions enabling a safe traffic at low and medium discharges, while at high water levels there are no obstacles to the flow of water and torrential sediment .